Carotid artery aneurysm: last among equals - Dhillon, Ajit Kaur (BMJ Case Rep, 2016)
A 66-year-old man presented initially with a swelling in the left side of the neck, which was confirmed to be a carotid artery aneurysm on ultrasonography. He was subsequently admitted reporting intermittent episodes of visual loss in the left eye and right arm weakness. Further imaging confirmed multiple, small acute infarcts in the left cerebral hemisphere. The patient underwent open repair of the aneurysm and made an uncomplicated recovery with no persisting neurological deficit.